Assessing the incidence of peripartum subclinical myocardial ischemia using the troponin T assay: an observational pilot study. Issue 1 (February 2015) - Smith, R.; Silversides, C.; Downey, K.; Newton, G.; Macarthur, A.
Highlights We assessed the incidence of peripartum subclinical myocardial ischemia using troponin T. We found a 4.3% incidence of raised assays amongst 140 women. Pre-defined risk factors did not enable prospective identification of these women.